Mengulas Hakikat Pendidik dalam Pendidikan Islam - Afiva, Nazwa (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2023)
This article is structured to describe the essence of educators in Islamic education. Writing this article aims to describe the meaning of educators, the requirements to become an educator, who can be said to be an educator, the goals of educators in Islamic education, and also the nature of educators in Islamic education. In writing this article using the descriptive method (library research) or literature study method. From this article, it was found that the essence of an educator in Islamic education is a person who has broad insight and is responsible as a guide and also a motivator for his student to be able to develop their potential through the skills, experience and expertise possessed by student.